Institutional arrangement for controlling corruption in public life: Karnataka experience - Sangita, S.N. (1995)
"Following a broader look at the concept and quantum of corruption, and the anti-corruption structure at the Central level, the author discusses different anti-corruption agencies of Karnataka. He then, on the basis of relevant data gathered by him, attempts to analyse the phenomenon of corruption in the state's public administration departments covering its nature, modes and causes. While high-lighting five critical factors contributing to growth of corruption, he lays greater emphasis on lack of political will"
Keywords: Political corruption - India - Karnataka; Political corruption